PENGELOLAAN KEUANGAN UNIT USAHA : STRATEGI PENGEMBANGAN KAPASITAS PONDOK PESANTREN - Renny Oktafia; Budi Haryanto (al-Uqud : Journal of Islamic Economics, 2018)
With the development of the era, many emerging modern pesantren, which has combined the science of religion and general science, in the learning materials for students santri. This study aims to explore how pesantren pondok seeks to increase its capacity, which can be done one of them through the development and management of business units boarding school. The method used is qualitative method, because it will reveal detailed data related to business unit financial management at boarding school, which can support operational activities and increase the capacity of pesantren cottage. In this research, it can be concluded that with the growth of business units owned by pesantren pondok, whose financial management is done regularly and correctly, can be known correctly the profit generated by each business unit. Where the benefits, which will be distributed for the development of boarding school.